The Influence of Foreign Ownership and Sustainability Committee on Sustainability Disclosure in Asean Regional Countries - Adhillah, Mona Nur; Meutia, Inten; Kartasari, Shelly Febriana (Dinasti Publisher, 2026)
This study is motivated by the increasing attention to sustainability practices in the ASEAN region, which requires companies to focus not only on financial performance but also on transparency and social and environmental responsibility. Foreign ownership and the existence of a sustainability committee are two governance factors that may influence the level of corporate sustainability disclosure. This study aims to examine the effect of foreign ownership and sustainability committee on sustainability disclosure among listed non-financial companies in five ASEAN countries (Indonesia, Malaysia, Singapore, Thailand, and Vietnam) during 2015–2023, with 1,083 firm-year observations. Sustainability disclosure is measured using the Refinitiv ESG Score, and the data are analyzed using panel data regression with EViews 12 software. The results show that foreign ownership has no significant effect on sustainability disclosure, suggesting that foreign investors have not fully encouraged sustainability reporting in ASEAN companies. Meanwhile, the existence of a sustainability committee has a positive and significant effect, confirming that internal governance mechanisms enhance corporate transparency and accountability. These findings support Stakeholder Theory and Agency Theory in explaining how governance structures and stakeholder pressures influence corporate sustainability reporting. This study contributes to academic literature and offers insights for regulators and corporate management to strengthen sustainability governance in developing ASEAN countries.